Islamic Consumer Behavior: A Bibliometric Analysis - Irfan Alfaridzi Ramadhan; Hari Mulyadi; Amir Machmud (International Economic and Finance Review, 2023)
This study aims to find out and analyze the main information, publication growth, the growth of this journal, growth based on institutions, researcher productivity, a publication based on the state, publication based on subjects, publications based on document types, thematics maps, network visualization, overlay visualization, density visualization, relationships between writers, dendrogram maps, and trend growth of keywords. The research uses the bibliometric method. Data collection by searching through the Scopus database with the keyword Islamic Consumer Behavior with Article Title Categories, Abstract, Keywords in the period 2006-2021. Data were analyzed by year, the author, the origin of the author, and the subject use of Microsoft Excel 2010. As for the map of publication development, it is analyzed using R-STUDIO software, and VosViewer. The results of research from this article itself found that the Malaysian state became the most contributing country related to the topic of Islamic consumer behavior with 89 most productive documents and writers on the topic of Islamic consumer behavior was Hanudin Amin from the Malaysian Sabah Universiti with 18 documents. The originality of this study is the first study of reviewing and mapping Islamic Consumer Behavior studies using bibliometric analysis, data used from year to year. All articles published in the journal have been reviewed in terms of methodology, state/state groups cases, and top tops/subtopics for future research. Keywords: Islamic consumer behavior, Islamic consumer, Consumer behavior, Bibliometric